2004
DOI: 10.5089/9781451851311.001
|View full text |Cite
|
Sign up to set email alerts
|

Does Regulatory Governance Matter for Financial System Stability? An Empirical Analysis

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.This paper provides empirical evidence that the quality of regulatory governancegovernance practices adopted by financial system regulators and supervisors-matters for financial sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 17 publications
2
63
0
2
Order By: Relevance
“…As a consequence, it can be concluded that in general, a development in national governance quality will lead to a decrease in banks fragility, the result of which is also relevant to the second hypothesis. The result of this research is also consistent with Das, Quintyn and Chenard [66] suggesting that the higher quality in governance, the higher stability that banks can achieve. The finding additionally aligns with those of Ngobo and Fouda [67] which is presented in the banking literatures that there is a positive relations between national governance quality and banks stability.…”
Section: A Effects Of Revenue Diversification On Financial Fragilitysupporting
confidence: 80%
“…As a consequence, it can be concluded that in general, a development in national governance quality will lead to a decrease in banks fragility, the result of which is also relevant to the second hypothesis. The result of this research is also consistent with Das, Quintyn and Chenard [66] suggesting that the higher quality in governance, the higher stability that banks can achieve. The finding additionally aligns with those of Ngobo and Fouda [67] which is presented in the banking literatures that there is a positive relations between national governance quality and banks stability.…”
Section: A Effects Of Revenue Diversification On Financial Fragilitysupporting
confidence: 80%
“…Recent work includes papers by Christofides, Mulder, and Tiffin (2003), who studied the impact of the observance of a variety of standards on spreads and ratings; Das, Quintyn, and Chenard (2004), who explored the link between financial sector soundness and regulatory governance; and Glennerster and Shin (2003), who focused on the effects of transparency on borrowing costs.…”
mentioning
confidence: 99%
“…Recent research asserting the positive influence of regulatory governance on financial stability includes Beck et al (2003), Das et al (2004), and Ponce (2009). Beck et al (2003) investigate the impact of various regulatory policies on the integrity of bank lending.…”
Section: Related Literaturementioning
confidence: 99%
“…The results of their ordered probit regression show that a higher degree of regulatory independence seems to reduce the likelihood that politicians or the financial industry will capture the agency. Das et al (2004) construct an index of regulatory governance based on the IMF's Financial Sector Assessment Program (FSAP). Banking sector stability is proxied by an index consisting of a weighted average of the capital adequacy ratio and the ratio of non-performing loans.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation